Bariatric surgeries in Espírito Santo State: characteristic and evolution of costs from 2008 to 2017 - Tatielle Rocha de Jesus; Erika Cardoso dos Reis (Universidade do Estado do Rio de Janeiro, 2020)
Introduction: Obesity is considered an important public health problem and bariatric surgery (BS) is one of the components of the line of care for its treatment and enabling the reduction of body weight. Objective: To analyze how resources, evolution and costs of procedures related to bariatric surgery in the state of Espírito Santo from 2008 to 2017. Methods: Observational, descriptive and retrospective study, using secondary data available in the public domain files from the Hospital Information System and the Hospital and Ambulatory Information Communication System, of the Ministry of Health. The calculated indicators were BS by sex and by age group, as well as expenses with hospital and professional services. Results: There was an increase in the number of bariatric surgeries and their costs over the ten years analyzed, of 184% and 483%, respectively. We also found that 87% (n = 2.923) of the procedures performed in the female public, which had a significant quantitative number of BS in the age group from 24 to 34 years old and that the costs represented 0.85% of hospital expenses in Espírito Santo. Conclusions: There is a need to discuss an articulation with the other services in the health care network to implement a line of effective care that includes, in addition to bariatric surgery, or health monitoring by other health services, especially by Primary Care.